Peranan Orang Tua dalam Mengembangkan Religiusitas Remaja di Desa Sidorahayu Kecamatan Abung Semuli Kabupaten Lampung Utara - Setiawati, Ayu; Aziz Q, Ikhwan; Wijaya, Adi (Attractive : Innovative Education Journal, 2024)
Educational background, type of work, and also the availability of time to accompany children are still serious obstacles in this regard. Based on the background above, the problem in this research is the role of parents in developing adolescent religiosity in Sidorahayu Village, Abung Semuli District, North Lampung Regency. This research was conducted with the aim of describing the various roles of parents in developing adolescent religiosity which will later have positive benefits and increase insight for readers. Apart from that, this research can also be a consideration for parents to create a conducive situation within the family. This type of research is field research, using a qualitative approach that uses questionnaires, observation and documentation as methods of collecting data. Data analysis is presented in an inductive qualitative descriptive manner which uses story descriptions of phenomena from respondents which are then compiled into data sources so that valid data results are obtained. Based on data analysis from research results, it was concluded that the role of parents who can develop religiosity aged 16 to 22 years is sending children to Islamic-based schools, mentoring and directing children's behavior, and implementing Islamic religious values ??in the family. Forms of developing religiosity, namely positive impacts (religiosity develops well in the form of istiqomah worship such as: praying on time, reading the Koran every evening, etc. In the case of mu'amalat being more polite, such as: speaking polite words) and negative impacts. Keywords: Developing Adolescent Religiosity, The Role of Parents